Improved performances in annealed P3HT-based dye sensitized solar cells (DSSC): A detailed morphological and spectroscopic investigation - Sai Santosh Kumar, R; Grancini, G; Abrusci, A; Snaith, H (2011)
We employ femtosecond transient absorption spectroscopy and atomic force microscopy on operating hybrid solid-state DSSC with P3HT as the hole transporter, to probe the effect of annealing on charge transfer dynamics and nanoscale morphology. © 2011 OSA.